The Effectiviness of Turmeric and Tamarind Herbal Medicine in Reducing Menstrual Pain Intensity - Cucuk Suwandi; Ni Luh Cica Kusumadewi; Ni Putu Widhi Adnyani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Menstrual cramps are pain that occurs during a woman's period, typically felt in the lower abdomen during the menstrual cycle. Effective non-pharmacological management includes administering turmeric and tamarind to reduce menstrual pain. Turmeric and tamarind contain curcumin and anthocyanins, which inhibit cyclooxygenase, thereby reducing inflammation and inhibiting uterine contractions. Interviews revealed that the menstrual pain was very bothersome. The aim of this study was to determine the effect of giving turmeric and tamarind herbal medicine on reducing the intensity of menstrual pain in nursing students at STIKES Advaita Medika Tabanan. The study employed a quantitative approach with a pre-experimental, one-group pretest-posttest design. Respondents were selected through purposive sampling of 16 people using a Numerical Rating Scale (NRS) pain assessment observation questionnaire. The Wilcoxon Signed Rank test was used for analysis. The decrease in menstrual pain scale after the intervention was given in the no pain category for 2 respondents (12.5%), mild pain for 11 respondents (68.8%), and moderate pain for 3 respondents (18.8%). The Wilcoxon Signed Rank test results showed a p-value of 0.001 (<0.05) and a Z-value of -3.286. The conclusion of this study is that there is an effect of giving turmeric and tamarind herbal medicine on reducing the intensity of menstrual pain in nursing students at STIKES Advaita Medika Tabanan.